Tracing Farmers’ Entrepreneurship and Communication Skills Using a Bibliometric Approach - Emi Widiyanti; Malik Cahyadin; Dwiningtyas Padmaningrum; Suminah Suminah; Prahastiwi Utari (AGRARIS: Journal of Agribusiness and Rural Development Research, 2023)
Farmers’ entrepreneurship and communication skills have been widely discussed in the literature. However, mapping the linkages and comparisons between the two needs to be addressed more. Therefore, this study attempts to map the literature on the two topics. The literature documents were collected from the Scopus database from 2012 to 2022. A bibliometric approach was employed. The findings revealed that literature documents on farmers’ entrepreneurship outnumbered those on farmers’ communication skills. The Journal of Sustainability and Journal of Rural Studies published the highest number of literature documents on the two topics. The highest number of literatures on farmers’ entrepreneurship was elaborated in developing countries, while that of farmers’ communication skills was studied in developed countries. Therefore, scholars and policymakers in developing and developed countries faced challenges in raising the number of literature documents on farmers’ entrepreneurship and communication skills to enhance agricultural business for both old and young generations.